Microglial innate memory and epigenetic reprogramming in neurological disorders - Martins-Ferreira, Ricardo (2021)
Microglia are myeloid-derived cells recognized as brain-resident macrophages. They act as the first and main line of immune defense in the central nervous system (CNS). Microglia have high phenotypic plasticity and are essential for regulating healthy brain homeostasis, and their dysregulation underlies the onset and progression of several CNS pathologies through impaired inflammatory responses. Aberrant microglial activation, following an inflammatory insult, is associated with epigenetic dysregulation in various CNS pathologies. Emerging data suggest that certain stimuli to myeloid cells determine enhanced or attenuated responses to subsequent stimuli. These phenomena, generally termed innate immune memory (IIM), are highly dependent on epigenetic reprogramming. Microglial priming has been reported in several neurological diseases and corresponds to a state of increased permissiveness or exacerbated response, promoted by continuous exposure to a chronic pro-inflammatory environment. In this article, we provide extensive evidence of these epigenetic-mediated phenomena under neurological conditions and discuss their contribution to pathogenesis and their clinical implications, including those concerning potential novel therapeutic approaches.